Determination of metals in tap water using atomic absorption spectrometry : a case study in Bandar Sunway residential area - Saraswathy Nalatambi, * (Sunway University College, 2009)
Metal contamination in water is a major component in the determination of water quality. Apparently, tap water qualities in many countries are affected by industrialization. The objective of this study was to detect metal concentration in tap water in the Bandar Sunway residential area. Tap water samples were collected from four different locations. The four sampling locations were Sunway University College, Sunway Villa Apartment, Sunway Condominium and PJS 7?11. Samples were analyzed using atomic absorption spectrometry to determine the concentration of dissolved metal. The metal analysis was done to detect zinc, cadmium, chromium, lead, magnesium, calcium and copper. The results obtained were compared with guidelines for drinking water quality such as the Environmental Protection Agency (EPA) and World Health Organization (WHO) guidelines. The study showed that the piping system which is over a decade old in the Sunway Villa Apartment affected levels of lead and copper in the water, but not zinc, cadmium, chromium, , magnesium and calcium.